Water-soluble components of Ancistrocladus cochinchinensis - Lien, Le Quynh; Cuc, Nguyen Thi; Tuan Anh, Hoang Le; Linh, Tran My; Giang, Vu Huong; Ban, Ninh Khac; Mai, Nguyen Chi; Hung, Trieu Quy; Hai Yen, Pham Thi; Kiem, Phan Van (Vietnam Journal of Science and Technology, 2017)
Using various chromatography methods, a saponin, ginsenoside Rg1 (1), and three phenolic glycosides, tortoside A (2), phlorizin (3), and 4-hydroxy-2-methoxyphenyl-6-O-syringyl-b-D-glucopyranoside (4) were isolated from the water-soluble fraction of Ancistrocladus cochinchinensis. Their structures were elucidated by 1D- and 2D-NMR spectroscopic analyses and comparison with those reported in the literature. Compound 1 was reported from A. cochinchinensis for the first time.